Do Minimum Wages Reduce Employment and Training? - Guntur Sugiyarto; Benjamin A. Endriga (Asian Development Bank (ADB), 2008)
Sovereign wealth funds (SWFs) are emerging as developing Asia's main policy tool for handling the region's excess foreign exchange reserves. SWFs represent a strategic shift of excess reserves from low-risk, low-return investments to high-risk, high-return investments, and are subject to a wide range of downside risks. The underlying nature of Asia's reserves, which are the consequence of the central bank's purchases of foreign exchange, means that those reserves have counterpart liabilities in the commercial banks that form the backbone of the region's financial systems. This suggests that the realization of SWFs' downside risks may have serious adverse effects on the region's domestic financial stability. The broader implication is that the transformation of Asia into a major exporter of capital raises the possibility that capital outflows can also be a direct source of financial instability in the region.
hdl:11540/1768
Keywords: 330; Mindestlohn; Personalbeschaffung; Betriebliches Bildungsmanagement; Indonesien